Is Self-Reported Physical Activity Participation Associated with Lower Health Services Utilization among Older Adults? Cross-Sectional Evidence from the Canadian Community Health Survey. (5th August 2015) - Fisher, Koren L.; Harrison, Elizabeth L.; Reeder, Bruce A.; Sari, Nazmi; Chad, Karen E.
Abstract : Purpose . To examine relationships between leisure time physical activity (LTPA) and health services utilization (H) in a nationally representative sample of community-dwelling older adults. Methods . Cross-sectional data from 56, 652 Canadian Community Health Survey respondents aged ≥ 50 years (48% M; 52% F; mean age 63.5 ± 10.2 years) were stratified into three age groups and analysed using multivariate generalized linear modeling techniques. Participants were classified according to PA level based on self-reported daily energy expenditure. Nonleisure PA (NLPA) was categorized into four levels ranging from mostly sitting to mostly lifting objects. Results . Active 50–65-year-old individuals were 27% less likely to report any GP consultations O R adj = 0.73 ; P < 0 . 001 and had 8% fewer GP consultations annually ( IR R adj = 0.92 ; P < 0 . 01 ) than their inactive peers. Active persons aged 65–79 years were 18% less likely than inactive respondents to have been hospitalized overnight in the previous year ( O R adj = 0.82, P < 0 . 05 ) . Higher levels of NLPA were significantly associated with lower levels of HSU, across all age groups. Conclusion . Nonleisure PA appeared to be a stronger predictor of all types of HSU, particularly in the two oldest age groups. Considering strategies that focus on reducing time spent in sedentary activities may have a positive impact on reducing the demand for health services.